2016
DOI: 10.1021/acsami.6b04038
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Iron Oxide Nanoparticle Seeded Growth of Nucleotide Coordinated Polymers

Abstract: Introducing functional molecules to the surface of magnetic iron oxide nanoparticles (NPs) is of critical importance. Most previously reported methods were focused on surface ligand attachment either by physisorption or covalent conjugation, resulting in limited ligand loading capacity. In this work, we report the seeded growth of a nucleotide coordinated polymer shell, which can be considered as a special form of adsorption by forming a complete shell. Among all the tested metal ions, Fe 3+ is the most effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Carbon-based nanomaterial, such as fullerene, graphene, carbon nanotubes and their derivatives, mimic various natural enzymes [97]. The peroxidase-like activity of CNTs have reported in another study [98].…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 95%
“…Carbon-based nanomaterial, such as fullerene, graphene, carbon nanotubes and their derivatives, mimic various natural enzymes [97]. The peroxidase-like activity of CNTs have reported in another study [98].…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 95%
“…While the nature of these interactions was relatively well‐known, its self‐assembly behavior was not investigated until recently. We explored Fe 3+ /AMP CPs in a similar way to the above Zn 2+ experiment . It was found that pH was important and CP nanoparticle formation was inhibited at acidic pH.…”
Section: Nucleobase Nucleoside or Nucleotide‐ Containing Cpsmentioning
confidence: 99%
“…In addition to proteins, it is also possible to entrap nanomaterials in such CPs. An interesting example is the growth of Fe 3+ /AMP on magnetic iron oxide nanoparticles (Figure A) . In this case, the surface of magnetic nanoparticles can be coated with a thin CP layer of a few nm as shown in Figure B–C.…”
Section: Applications Of Nucleotide‐containing Cpsmentioning
confidence: 99%
“…To solve these issues, immobilization techniques are considered, because binding of free enzymes to supports limits their mobility [8]. What is more, some immobilized enzymes could show more robust activity than free enzymes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their mild polymerization conditions, porosity and high guest-entrapment efficiency [11], CPs could play important roles in many fields, including catalysis [12], biological detection [28], imaging [29,30], gas storage [31] and drug delivery [32].…”
Section: Introductionmentioning
confidence: 99%